Developing Teacher Contextual Performance through School Organizational Culture and Cultural Intelligence - Widodo, Widodo (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research aims to explore the influence of school organizational culture on teachers' contextual performance with the mediation of cultural intelligence. To achieve this goal, a survey was conducted using a questionnaire in the form of a Likert scale, which was given to 275 elementary school teachers as a sample. Data analysis uses structural equation modeling. The results show that school organizational culture and cultural intelligence significantly affect teacher contextual performance, cultural intelligence, and teacher contextual performance through cultural intelligence. Thus, this research promotes a new empirical model of the influence of school organizational culture on teachers' contextual performance through cultural intelligence. These findings provide theoretical contributions to developing performance literature, especially contextual performance about organizational culture and cultural intelligence. These findings also provide practical implications for school management to consider school organizational culture and cultural intelligence as instruments for improving teacher contextual performance. Therefore, researchers and practitioners can consider these new findings to develop teachers' contextual performance in the future.